2012
DOI: 10.1371/journal.pone.0029819
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Risk Variant HLA-DRB1*1501 Associates with High Expression of DRB1 Gene in Different Human Populations

Abstract: The human leukocyte antigen (HLA) DRB1*1501 has been consistently associated with multiple sclerosis (MS) in nearly all populations tested. This points to a specific antigen presentation as the pathogenic mechanism though this does not fully explain the disease association. The identification of expression quantitative trait loci (eQTL) for genes in the HLA locus poses the question of the role of gene expression in MS susceptibility. We analyzed the eQTLs in the HLA region with respect to MS-associated HLA-var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 45 publications
9
79
1
Order By: Relevance
“…Some research has found that a variety of HLA-B gene subtypes is related to the progression of HIV infection (Gao et al, 2001;Carrington and O'Brien, 2003). We also confirmed that loci rs9268853 and rs9271100, which are associated with ulcerative colitis (Pereyra et al, 2010) and systemic lupus erythematosus (Han et al, 2009;Alcina et al, 2012), affect the expression of HLA class II, DR beta 1 (HLA-DRB1) in lymphoid cell lines (Montgomery et al, 2010). The results showed that the eQTL genes shared among tissues are consistent with disease risk genes and loci in GWAS.…”
Section: Validation Through Gwas Omim and Text Miningsupporting
confidence: 81%
“…Some research has found that a variety of HLA-B gene subtypes is related to the progression of HIV infection (Gao et al, 2001;Carrington and O'Brien, 2003). We also confirmed that loci rs9268853 and rs9271100, which are associated with ulcerative colitis (Pereyra et al, 2010) and systemic lupus erythematosus (Han et al, 2009;Alcina et al, 2012), affect the expression of HLA class II, DR beta 1 (HLA-DRB1) in lymphoid cell lines (Montgomery et al, 2010). The results showed that the eQTL genes shared among tissues are consistent with disease risk genes and loci in GWAS.…”
Section: Validation Through Gwas Omim and Text Miningsupporting
confidence: 81%
“…This finding therefore suggests that the linked causal variants in these regions are likely to be expression quantitative trait loci (eQTL), at which polymorphism affects the expression of one or more transcripts. Indeed, the data obtained on candidate genes for several autoimmune diseases strongly support the hypothesis that most of the genetically encoded risk of disease is conferred by eQTL [38,71,103,[156][157][158][159][160][161][162][163].…”
Section: From Genes To Functionmentioning
confidence: 67%
“…In particular, the association between HLA-class II genes and the relative risk for MS has been investigated in several populations 1,6,9 , and a link between HLA-DRB1* and MS susceptibility in Brazilian patients has already been reported 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The genetic components of MS pathogenesis are quite complex 6 , and the human leukocyte antigen (HLA) class II genes (6p21.3) appear to play an important role in determining the risk for MS. For example, the HLA-DRB1*15:01 allele is consistently associated with MS 6 . Studies performed on North American and European populations revealed an association between the HLA-DRB1*15:01, -DQA1*01:02 and -DQB1*06:02 alleles and the development of MS 7 , and these alleles have also been linked to MS in the Brazilian population 8,9,10 .…”
mentioning
confidence: 99%